Are we making Inroads? A randomized controlled trial of a psychologist-supported, web-based, cognitive behavioral therapy intervention to reduce anxiety and hazardous alcohol use among emerging adults. (September 2021) - Stapinski, Lexine A.; Prior, Katrina; Newton, Nicola C.; Biswas, Raaj Kishore; Kelly, Erin; Deady, Mark; Lees, Briana; Teesson, Maree; Baillie, Andrew J.
Abstract: Background: Anxiety and alcohol use disorders are common and disabling conditions that people typically endure for many years before accessing treatment. The link between anxiety and alcohol use is well-established, with these issues commonly emerging and/or escalating during emerging adulthood. This randomized controlled trial evaluated a psychologist-supported, web-based intervention, designed with and for emerging adults, that aims to promote adaptive coping strategies, and prevent anxiety and alcohol use from progressing to chronic, mutually-reinforcing disorders. Methods: Between December 2017 and September 2018, 123 emerging adults (aged 17–24) reporting anxiety symptoms and hazardous alcohol use were randomized to receive the Inroads or control (assessment plus alcohol information) intervention. The Inroads program combined five web-based cognitive behavioral therapy modules with weekly psychologist support via email/phone. Primary outcomes were alcohol consumption, severity of alcohol-related consequences, and general anxiety symptoms, assessed at baseline, 2 and 6-months post-baseline. Secondary outcomes included hazardous alcohol use and social anxiety. Trial Registration: Prospectively registered in the Australian New Zealand Clinical Trials Registry, ACTRN12617001609347. Findings: Alcohol consumption and associated consequences reduced in both groups, with the Inroads group reporting greater alcohol reductions by 6-month follow-up (mean difference -0.74, 95% CI: -1.47 to -0.01, d  = 0.24). Relative to controls, hazardous alcohol use reduced among Inroads participants at both follow-ups (2-month mean difference -2.14, 95% CI: -4.06 to -0.22). Inroads participants also reported reduced symptoms of general (mean difference -3.06, 95% CI: -4.97 to -1.15, d  = 0.88) and social anxiety (mean difference -3.21, 95% CI: -6.34 to -0.07, d  = 0.32) at 2-month follow-up, with improvements in social anxiety sustained at 6-months. Interpretation: The Inroads program demonstrated beneficial effects on alcohol consumption, hazardous alcohol use, and anxiety symptoms. The web-based format is aligned with youth treatment preferences and can be delivered at scale to achieve wide dissemination and reduce the significant burden associated with these chronic, mutually reinforcing conditions. Funding: Australian Rotary Health, Australian National Health and Medical Research Council.